Between the Inquisition and the king: the favorites and the secretaries of State (1580-1736) - López-Salazar, Ana Isabel (2019)
The integration of Portugal in the Hispanic Monarchy caused a problem in the communication between the Portuguese Inquisition and the Crown, at the time located in Madrid. To prevent the constant intervention of the Council of Portugal and the viceroys in the matters of the Holy Office, the Inquisition tried to establish several ways to communicate directly with the king. The most original was the integration of the favorites and the secretaries of State in the inquisitorial institution. After the Restoration, the secretaries of State conserved the position of secretaries of the Holy Office until 1736, demonstrating the efficiency of certain institutional innovations of the Philippine period.